PERANCANGAN SISTEM KONTROL ROBOT LENGAN YANG DIHUBUNGKAN DENGAN KOMPUTER - Nugraha, Deny Wiria (MEKTEK, 2010)
The robots were the result of technology development which used to help human being, both in industrial orbeyond the industrial. In the beginning, the robots were such automatic machine which the system stillfeature as mechanic automatic with movement which controlled by simple control system. With thedevelopment of microcomputer, control system in the robot being developed by use the computer where themovement control and their sensor handled by the computer. It make the robot more skilled to handle anykind of jobs. In this study, the authors designed a type of arm robot. The planning of control system of armrobot using computer as data processor with interface PPI-8255 and parallel port (LPT1). Theimplementation of this study were one robot which made from iron frame by the prior driver power that weresix DC motors which use transmission system with gear wheel characteristic, and as the movement/positionsensor used encoder plates which will read by optocoupler. The system planning include generally mechanicsystem planning and hardware system planning